High-strength polypropylene composite material for filter plate and preparation method of high-strength polypropylene composite material

By modifying nano calcium carbonate and glass fibers and melting and blending with polypropylene and other materials, high-strength polypropylene composite materials are prepared, which solves the problems of poor impact resistance and general mechanical strength of the polypropylene filter plate, and realizes the The material has improved its high strength, toughness and heat resistance.

CN119391086AActive Publication Date: 2025-02-07YANTAI HEXIN ENVIRONMENTAL PROTECTION EQUIP CO LTD

Patent Information

Application Number
CN202510000601.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-02-07
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

Polypropylene filter plates have poor impact resistance and average mechanical strength, and the existing modified polypropylene composite materials have poor stability under high temperature and high pressure conditions.

Method used

By modifying nano calcium carbonate with L-lysine, aminated calcium carbonate is formed, and glass fibers are alkenized and modified, and combined with polypropylene, polyimide, nylon 6 and other materials for melt blending. Prepare high-strength polypropylene composite materials.

Benefits of technology

The impact resistance, mechanical strength and heat resistance of polypropylene composite materials are significantly improved, ensuring the stability and performance of the material under high temperature and high pressure conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and particularly discloses a high-strength polypropylene composite material for a filter plate and a preparation method of the high-strength polypropylene composite material. The preparation method of the polypropylene composite material comprises the following steps: uniformly mixing polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, a maleic anhydride grafted styrene-butadiene-styrene copolymer, aminated calcium carbonate, modified glass fiber, an antioxidant and a lubricant according to a mass ratio of 100: (12-18): (2-5): (1-2): (3-5): (3-7): (6-10): (0.2-0.5): (0.1-0.3), carrying out melt blending, extruding, cooling, granulating, and carrying out extrusion molding to obtain the polypropylene composite material. Through the synergistic effect of the nano calcium carbonate and the glass fibers, the mechanical property of polypropylene is improved, all the raw materials are crosslinked to form a uniform network structure, more energy is absorbed when a matrix is impacted by external force, and it is guaranteed that the filter pressing plate is not damaged when deforming under the high-temperature and high-pressure conditions; the obtained polypropylene composite material is high in strength, good in heat resistance and excellent in comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a high-strength polypropylene composite material for a filter plate and a preparation method thereof. Background Art

[0002] A filter press is an environmentally friendly dehydration equipment that uses a filter medium to exert a certain pressure on an object to separate solids and liquids. It is widely used in the chemical, pharmaceutical, metallurgical, food, ceramic and other industries. The filter plate is the core filter component of the filter press. Its performance has a great influence on the performance of the filter press and determines the production strength and separation accuracy of the filter press. Most of the filter plates used in traditional filter presses are made of rubber, which has good toughness, but low strength and is not corrosion-resistant. The product quality is unstable and the price is high.

[0003] Polypropylene is a semi-crystalline general-purpose plastic with low price, low density, high strength and good chemical stability. It is widely used in various fields of production and life. With the rapid development of polypropylene materials, polypropylene materials have become an ideal substitute for general engineering plastics in some engineering application fields, and filter plates of filter presses have also begun to use polypropylene materials. However, the impact resistance of single polypropylene materials is poor, and the heat resistance also needs to be improved. Chinese patent application CN108752738A discloses a high temperature and high pressure resistant filter plate of a filter press and a preparation method thereof. The filter plate is made of polypropylene, titanate coupling agent, calcium carbonate, toughening agent, modified zeolite, wetting agent and antioxidant. The raw materials of the filter plate are easy to obtain and low in cost, and have good high temperature and high pressure resistance, but the dispersibility between the raw materials is poor, the stability is general, and the impact resistance is poor. Chinese patent application CN113637260A discloses a modified polypropylene composite material filter press filter plate and a continuous preparation method thereof, wherein the filter plate comprises high melt strength polypropylene, glass fiber masterbatch, composite calcium carbonate, β nucleating agent, composite coupling agent, calcium stearate, composite antioxidant and high temperature resistant agent. The modified polypropylene composite material filter press filter plate has excellent tensile strength and improved heat resistance, but has average impact resistance and poor toughness. Too much glass fiber masterbatch is added, which easily causes agglomeration, affects the performance of the composite material and affects the stability of the filtration system. Therefore, it is very necessary to provide a polypropylene material with excellent heat resistance, high strength and toughness. Summary of the invention

[0004] 1. Technical issues to be resolved In order to solve the above technical problems, the present invention provides a high-strength polypropylene composite material for filter plates and a preparation method thereof, which solves the problems of poor impact resistance and general mechanical strength of polypropylene filter plates.

[0005] (II) Technical solution In order to achieve the above object, the present invention discloses a method for preparing a high-strength polypropylene composite material for a filter plate, comprising the following steps: Step 1: Ultrasonically disperse nano calcium carbonate into deionized water, and after uniform dispersion, add L-lysine, heat, mix, and react. After the reaction is completed, filter, wash with anhydrous ethanol and deionized water, and dry at 60° C. for 24 hours to obtain amino calcium carbonate; Step 2: Evenly mix the ethanol solution and γ-methacryloxypropyltrimethoxysilane, add glass fiber, stir, adjust the pH to 4.5 with acetic acid, heat under reflux in a nitrogen atmosphere, react, and after the reaction is completed, filter, wash with anhydrous ethanol, and vacuum dry at 60° C. for 12 hours to obtain olefinic glass fiber; Step 3: Mix the olefinized glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, and acrylamide, add an initiator in a nitrogen atmosphere, heat and stir to react, and after the reaction, wash with anhydrous ethanol and dry at 60° C. for 12 hours to obtain a modified glass fiber; Step 4: Evenly mix polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer (SBS-g-MAH), amino calcium carbonate, modified glass fiber, antioxidant, and lubricant, perform melt blending, extrude, and cool to obtain a high-strength polypropylene composite material for filter plates.

[0006] Preferably, in step 1, the mass ratio of nano-calcium carbonate, deionized water and L-lysine is 100:1000-1500:8-15.

[0007] Preferably, the reaction temperature in step 1 is 65-75° C., and the reaction time is 2-3 h.

[0008] Preferably, in the step 2, the mass ratio of the ethanol solution, γ-methacryloxypropyltrimethoxysilane and the glass fiber is 6800-7500:15-20:100.

[0009] Preferably, the reaction temperature in step 2 is 95-105° C., and the reaction time is 4-6 h.

[0010] Preferably, the ethanol solution in step 2 is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 3:1.

[0011] Preferably, in step three, the mass ratio of olefinated glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, acrylamide, and initiator is 100:3500-4500:25-35:8-15:6-10:2-5.

[0012] Preferably, the initiator in step three is benzoyl peroxide.

[0013] Preferably, the reaction temperature in step 3 is 75-85° C., and the reaction time is 2-4 h.

[0014] Preferably, in step 4, the mass ratio of polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, amino calcium carbonate, modified glass fiber, antioxidant, and lubricant is 100:12-18:2-5:1-2:3-5:3-7:6-10:0.2-0.5:0.1-0.3.

[0015] Preferably, the antioxidant in step 4 includes one or more of antioxidant 168, antioxidant 1010, and antioxidant 1098.

[0016] Preferably, the lubricant in step 4 includes one or more of polypropylene wax, stearic acid acetamide, and polyethylene wax.

[0017] Preferably, the melt blending in the step 4 is carried out in a twin-screw extruder, the rotation speed of the twin-screw extruder is 140-150 rpm, and the twin-screw extruder is provided with five temperature zones according to the forward direction of the material, and the temperatures in the temperature zones are 135-150°C, 175-190°C, 205-215°C, 225-235°C, and 240-250°C, respectively.

[0018] A high-strength polypropylene composite material for filter plates is prepared by adopting the method for preparing the high-strength polypropylene composite material for filter plates.

[0019] 3. Beneficial technical effects In the present invention, L-lysine is used to modify nano calcium carbonate. 2+ Chemical bonding with the carboxyl group in L-lysine is carried out to obtain amino calcium carbonate, and a large number of amino groups are introduced into nano calcium carbonate. γ-methacryloxypropyl trimethoxysilane is used to modify glass fiber, and alkenyl groups are introduced into the surface of glass fiber to obtain alkenyl glass fiber. Alkenyl glass fiber, acrylic acid, glycidyl methacrylate, and acrylamide are polymerized in situ under the action of an initiator to obtain modified glass fiber, and a large number of amino, carboxyl, and epoxy active groups are introduced into the modified glass fiber. Using polypropylene resin as a matrix, polyimide resin, compatibilizer maleic anhydride grafted polypropylene, nylon 6 resin, maleic anhydride grafted styrene butadiene styrene copolymer elastomer, amino calcium carbonate, modified glass fiber, antioxidant, and lubricant are melt-blended in a twin-screw extruder to obtain a high-strength polypropylene composite material for filter plates.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The polypropylene in the present invention has good heat resistance, chemical stability, mechanical properties and processing properties. The comprehensive properties of the polypropylene material can be further improved by adding other fillers, resins and additives. Nano calcium carbonate has abundant specific surface area and surface active sites, excellent heat resistance and mechanical properties, and can effectively enhance the mechanical properties and heat resistance of the matrix. Nano calcium carbonate can fill the defects and gaps of the matrix through diffusion and interface effects, improve the density and crystallinity of the matrix, improve the mechanical properties and heat resistance of the matrix, form an effective stress transfer network, effectively absorb deformation work, improve the toughness of the matrix, and improve the impact resistance of the material. Glass fiber has the characteristics of high tensile strength, good elasticity and good corrosion resistance. It can absorb a large amount of impact energy. When added to the polypropylene matrix, it can play the role of a skeleton in the matrix, improve the overall strength of the material, and when the material is subjected to external force, it can withstand stress, slow down the deformation of the material, prevent the material from being damaged, and improve the heat resistance of the matrix.

[0021] (2) The polyimide resin in the present invention has excellent high temperature resistance. After being mixed with the polypropylene matrix, it can greatly improve the high temperature resistance of the polypropylene matrix. Nylon 6 has high strength and toughness, and can improve the mechanical properties of the body such as tensile strength and flexural strength. Maleic anhydride grafted styrene butadiene styrene copolymer has good elasticity, excellent toughness and strength, and can improve the toughness of the matrix and improve the impact resistance. Polyimide and nylon 6 contain a large amount of amide matrix, and maleic anhydride grafted styrene butadiene styrene copolymer contains anhydride groups.

[0022] (3) In the present invention, nano calcium carbonate and glass fiber are modified to effectively avoid the agglomeration of the two, and can be evenly dispersed in the polypropylene matrix, thereby improving the compatibility between the raw materials. The synergistic effect between nano calcium carbonate and glass fiber can jointly bear external forces, improve the mechanical properties of polypropylene, and obtain high-strength polypropylene. The raw materials can be cross-linked to form a uniform network structure, which plays an effective buffering role when the matrix is ​​impacted by external forces, disperses stress, avoids stress concentration, prevents crack extension, and has a toughening effect. The raw materials have excellent compatibility and dispersibility, can effectively destroy the regularity of the polypropylene continuous phase matrix, increase the amorphous area, present an island-type microstructure, make the molecular chain segments easier to move, can absorb more energy, and induce the shear band to be blocked and turned, effectively inhibiting the silver streaks from developing to a deeper level, ensuring that the filter press plate is not damaged when it is deformed under high temperature and high pressure conditions. The obtained polypropylene composite material has high strength, good heat resistance, and excellent comprehensive performance. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] Example 1 A method for preparing a high-strength polypropylene composite material for a filter plate comprises the following steps: (1) Ultrasonic dispersion of nano-calcium carbonate in deionized water, after uniform dispersion, adding L-lysine, wherein the mass ratio of nano-calcium carbonate, deionized water, and L-lysine is 100:1000:8, heating, mixing, reacting at 65°C for 3 hours, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water, and drying at 60°C for 24 hours to obtain amino calcium carbonate; (2) mixing an ethanol solution and γ-methacryloxypropyltrimethoxysilane evenly, wherein the ethanol solution is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 3:1, adding glass fiber, wherein the mass ratio of the ethanol solution, γ-methacryloxypropyltrimethoxysilane and glass fiber is 6800:15:100, stirring, adjusting the pH to 4.5 with acetic acid, heating under reflux in a nitrogen atmosphere, reacting at 95°C for 6h, and after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 12h to obtain olefinic glass fiber; (3) mixing olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, and acrylamide, adding initiator benzoyl peroxide in a nitrogen atmosphere, wherein the mass ratio of olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, acrylamide, and initiator benzoyl peroxide is 100:3500:25:8:6:2, heating and stirring, reacting at 75°C for 4h, washing with anhydrous ethanol after the reaction, and drying at 60°C for 12h to obtain modified glass fiber; (4) Polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, amino calcium carbonate, modified glass fiber, antioxidant 1010, and lubricant polyethylene wax in a mass ratio of 100:12:2:1:3:3:6:0.2:0.1 are mixed uniformly and melt-blended. The melt-blending is carried out in a twin-screw extruder. The speed of the twin-screw extruder is 140 rpm. The twin-screw extruder is provided with five temperature zones according to the forward direction of the material. The temperatures in the temperature zones are 135°C, 175°C, 205°C, 225°C, and 240°C, respectively. The material is extruded and cooled to obtain a high-strength polypropylene composite material for a filter plate.

[0025] Example 2 A method for preparing a high-strength polypropylene composite material for a filter plate comprises the following steps: (1) Ultrasonic dispersion of nano-calcium carbonate in deionized water, after uniform dispersion, adding L-lysine, wherein the mass ratio of nano-calcium carbonate, deionized water, and L-lysine is 100:1200:10, heating, mixing, reacting at 70°C for 2.5 hours, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water, and drying at 60°C for 24 hours to obtain amino calcium carbonate; (2) mixing an ethanol solution and γ-methacryloxypropyltrimethoxysilane evenly, wherein the ethanol solution is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 3:1, adding glass fiber, wherein the mass ratio of the ethanol solution, γ-methacryloxypropyltrimethoxysilane and glass fiber is 7000:16:100, stirring, adjusting the pH to 4.5 with acetic acid, heating under reflux in a nitrogen atmosphere, reacting at 100°C for 4.5 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 12 hours to obtain olefinic glass fiber; (3) Stirring and mixing olefinized glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, and acrylamide, adding initiator benzoyl peroxide in a nitrogen atmosphere, wherein the mass ratio of olefinized glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, acrylamide, and initiator benzoyl peroxide is 100:3800:28:10:7:3, heating and stirring, reacting at 80°C for 2.5h, washing with anhydrous ethanol after the reaction, and drying at 60°C for 12h to obtain modified glass fiber; (4) Polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, amino calcium carbonate, modified glass fiber, antioxidant 1010, and lubricant polyethylene wax in a mass ratio of 100:14:3:1.5:3.5:4:7:0.3:0.2 are mixed uniformly and melt-blended. The melt-blending is carried out in a twin-screw extruder. The speed of the twin-screw extruder is 145 rpm. The twin-screw extruder is provided with five temperature zones according to the forward direction of the material. The temperatures of the temperature zones are 140°C, 180°C, 210°C, 228°C, and 245°C, respectively. The material is extruded and cooled to obtain a high-strength polypropylene composite material for a filter plate.

[0026] Example 3 A method for preparing a high-strength polypropylene composite material for a filter plate comprises the following steps: (1) Ultrasonic dispersion of nano-calcium carbonate in deionized water, after uniform dispersion, adding L-lysine, wherein the mass ratio of nano-calcium carbonate, deionized water, and L-lysine is 100:1400:14, heating, mixing, reacting at 70°C for 2.5 hours, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water, and drying at 60°C for 24 hours to obtain amino calcium carbonate; (2) mixing an ethanol solution and γ-methacryloxypropyltrimethoxysilane evenly, wherein the ethanol solution is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 3:1, adding glass fiber, wherein the mass ratio of the ethanol solution, γ-methacryloxypropyltrimethoxysilane and glass fiber is 7400:18:100, stirring, adjusting the pH to 4.5 with acetic acid, heating under reflux in a nitrogen atmosphere, reacting at 100°C for 5.5h, after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 12h to obtain olefinic glass fiber; (3) mixing olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, and acrylamide, adding initiator benzoyl peroxide in a nitrogen atmosphere, wherein the mass ratio of olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, acrylamide, and initiator benzoyl peroxide is 100:4200:32:12:9:4, heating and stirring, reacting at 80°C for 3.5h, washing with anhydrous ethanol after the reaction, and drying at 60°C for 12h to obtain modified glass fiber; (4) Polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, amino calcium carbonate, modified glass fiber, antioxidant 1010, and lubricant polyethylene wax in a mass ratio of 100:14:3:1.5:3.5:4:7:0.3:0.2 are mixed uniformly and melt-blended. The melt-blending is carried out in a twin-screw extruder. The speed of the twin-screw extruder is 145 rpm. The twin-screw extruder is provided with five temperature zones according to the forward direction of the material. The temperatures of the temperature zones are 140°C, 180°C, 210°C, 228°C, and 245°C, respectively. The material is extruded and cooled to obtain a high-strength polypropylene composite material for a filter plate.

[0027] Example 4 A method for preparing a high-strength polypropylene composite material for a filter plate comprises the following steps: (1) Ultrasonic dispersion of nano-calcium carbonate in deionized water, after uniform dispersion, adding L-lysine, wherein the mass ratio of nano-calcium carbonate, deionized water, and L-lysine is 100:1400:14, heating, mixing, reacting at 70°C for 2.5 hours, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water, and drying at 60°C for 24 hours to obtain amino calcium carbonate; (2) mixing an ethanol solution and γ-methacryloxypropyltrimethoxysilane evenly, wherein the ethanol solution is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 3:1, adding glass fiber, wherein the mass ratio of the ethanol solution, γ-methacryloxypropyltrimethoxysilane and glass fiber is 7400:18:100, stirring, adjusting the pH to 4.5 with acetic acid, heating under reflux in a nitrogen atmosphere, reacting at 100°C for 5.5h, after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 12h to obtain olefinic glass fiber; (3) mixing olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, and acrylamide, adding initiator benzoyl peroxide in a nitrogen atmosphere, wherein the mass ratio of olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, acrylamide, and initiator benzoyl peroxide is 100:4200:32:12:9:4, heating and stirring, reacting at 80°C for 3.5h, washing with anhydrous ethanol after the reaction, and drying at 60°C for 12h to obtain modified glass fiber; (4) Polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, amino calcium carbonate, modified glass fiber, antioxidant 1010, and lubricant polyethylene wax in a mass ratio of 100:16:4:1.8:4.5:6:9:0.4:0.2 are mixed uniformly and melt-blended. The melt-blending is carried out in a twin-screw extruder. The speed of the twin-screw extruder is 148 rpm. The twin-screw extruder is provided with five temperature zones according to the forward direction of the material. The temperatures of the temperature zones are 145°C, 185°C, 210°C, 232°C, and 248°C, respectively. The material is extruded and cooled to obtain a high-strength polypropylene composite material for a filter plate.

[0028] Example 5 A method for preparing a high-strength polypropylene composite material for a filter plate comprises the following steps: (1) Ultrasonic dispersion of nano-calcium carbonate in deionized water, after uniform dispersion, adding L-lysine, wherein the mass ratio of nano-calcium carbonate, deionized water and L-lysine is 100:1500:15, heating, mixing, reacting at 75°C for 2h, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water, and drying at 60°C for 24h to obtain amino calcium carbonate; (2) mixing an ethanol solution and γ-methacryloxypropyltrimethoxysilane uniformly, wherein the ethanol solution is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 3:1, adding glass fiber, wherein the mass ratio of the ethanol solution, γ-methacryloxypropyltrimethoxysilane and glass fiber is 7500:20:100, stirring, adjusting the pH to 4.5 with acetic acid, heating under reflux in a nitrogen atmosphere, reacting at 105°C for 4 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 12 hours to obtain olefinic glass fiber; (3) mixing olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, and acrylamide, adding initiator benzoyl peroxide in a nitrogen atmosphere, wherein the mass ratio of olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, acrylamide, and initiator benzoyl peroxide is 100:4500:35:15:10:5, heating and stirring, reacting at 85°C for 2h, washing with anhydrous ethanol after the reaction, and drying at 60°C for 12h to obtain modified glass fiber; (4) Polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, amino calcium carbonate, modified glass fiber, antioxidant 1010, and lubricant polyethylene wax in a mass ratio of 100:18:5:2:5:7:10:0.5:0.3 are mixed uniformly and melt-blended. The melt-blending is carried out in a twin-screw extruder. The speed of the twin-screw extruder is 150 rpm. The twin-screw extruder is provided with five temperature zones according to the forward direction of the material. The temperatures of the temperature zones are 150° C., 190° C., 215° C., 235° C., and 250° C., respectively. Extrusion and cooling are performed to obtain a high-strength polypropylene composite material for filter plates.

[0029] Comparative Example 1 A method for preparing a polypropylene composite material comprises the following steps: (1) Ultrasonic dispersion of nano-calcium carbonate in deionized water, after uniform dispersion, adding L-lysine, wherein the mass ratio of nano-calcium carbonate, deionized water, and L-lysine is 100:1400:14, heating, mixing, reacting at 70°C for 2.5 hours, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water, and drying at 60°C for 24 hours to obtain amino calcium carbonate; (2) Polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, amino calcium carbonate, glass fiber, antioxidant 1010, and lubricant polyethylene wax in a mass ratio of 100:16:4:1.8:4.5:6:9:0.4:0.2 are mixed uniformly and melt-blended. The melt-blending is carried out in a twin-screw extruder. The speed of the twin-screw extruder is 148 rpm. The twin-screw extruder is provided with five temperature zones according to the forward direction of the material. The temperatures of the temperature zones are 145°C, 185°C, 210°C, 232°C, and 248°C, respectively. Extrusion and cooling are performed to obtain a polypropylene composite material.

[0030] Comparative Example 2 A method for preparing a polypropylene composite material comprises the following steps: (1) Evenly mixing an ethanol solution and γ-methacryloxypropyltrimethoxysilane, wherein the ethanol solution is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 3:1, adding glass fiber, wherein the mass ratio of the ethanol solution, γ-methacryloxypropyltrimethoxysilane and glass fiber is 7400:18:100, stirring, adjusting the pH to 4.5 with acetic acid, heating under reflux in a nitrogen atmosphere, reacting at 100° C. for 5.5 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60° C. for 12 hours to obtain olefinic glass fiber; (2) mixing olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, and acrylamide, adding initiator benzoyl peroxide in a nitrogen atmosphere, wherein the mass ratio of olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, acrylamide, and initiator benzoyl peroxide is 100:4200:32:12:9:4, heating and stirring, reacting at 80°C for 3.5h, washing with anhydrous ethanol after the reaction, and drying at 60°C for 12h to obtain modified glass fiber; (3) Polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, nano calcium carbonate, modified glass fiber, antioxidant 1010, and lubricant polyethylene wax in a mass ratio of 100:16:4:1.8:4.5:6:9:0.4:0.2 are mixed uniformly and melt blended. The melt blending is carried out in a twin-screw extruder. The speed of the twin-screw extruder is 148 rpm. The twin-screw extruder is provided with five temperature zones according to the forward direction of the material. The temperatures of the temperature zones are 145°C, 185°C, 210°C, 232°C, and 248°C, respectively. Extrusion and cooling are performed to obtain a polypropylene composite material.

[0031] Comparative Example 3 A method for preparing a polypropylene composite material comprises the following steps: (1) Polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, nano calcium carbonate, glass fiber, antioxidant 1010, and lubricant polyethylene wax in a mass ratio of 100:16:4:1.8:4.5:6:9:0.4:0.2 are mixed uniformly and melt-blended. The melt-blending is carried out in a twin-screw extruder. The speed of the twin-screw extruder is 148 rpm. The twin-screw extruder is provided with five temperature zones according to the forward direction of the material. The temperatures of the temperature zones are 145° C., 185° C., 210° C., 232° C., and 248° C., respectively. The material is extruded and cooled to obtain a polypropylene composite material.

[0032] Comparative Example 4 A method for preparing a polypropylene composite material comprises the following steps: (1) Ultrasonic dispersion of nano-calcium carbonate in deionized water, after uniform dispersion, adding L-lysine, wherein the mass ratio of nano-calcium carbonate, deionized water, and L-lysine is 100:1400:14, heating, mixing, reacting at 70°C for 2.5 hours, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water, and drying at 60°C for 24 hours to obtain amino calcium carbonate; (2) mixing an ethanol solution and γ-methacryloxypropyltrimethoxysilane evenly, wherein the ethanol solution is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 3:1, adding glass fiber, wherein the mass ratio of the ethanol solution, γ-methacryloxypropyltrimethoxysilane and glass fiber is 7400:18:100, stirring, adjusting the pH to 4.5 with acetic acid, heating under reflux in a nitrogen atmosphere, reacting at 100°C for 5.5h, after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 12h to obtain olefinic glass fiber; (3) mixing olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, and acrylamide, adding initiator benzoyl peroxide in a nitrogen atmosphere, wherein the mass ratio of olefinic glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, acrylamide, and initiator benzoyl peroxide is 100:4200:32:12:9:4, heating and stirring, reacting at 80°C for 3.5h, washing with anhydrous ethanol after the reaction, and drying at 60°C for 12h to obtain modified glass fiber; (4) Polypropylene, maleic anhydride grafted polypropylene, amino calcium carbonate, modified glass fiber, antioxidant 1010, and lubricant polyethylene wax in a mass ratio of 122.3:4:6:9:0.4:0.2 are mixed uniformly and melt-blended. The melt-blending is carried out in a twin-screw extruder. The speed of the twin-screw extruder is 148 rpm. The twin-screw extruder is provided with five temperature zones according to the forward direction of the material. The temperatures in the temperature zones are 145° C., 185° C., 210° C., 232° C., and 248° C., respectively. The material is extruded and cooled to obtain a polypropylene composite material.

[0033] The nano calcium carbonate in the present invention is purchased from Guangxi Warner Technology Co., Ltd., with an average particle size of 20 nm and a purity of ≥99.99%; the glass fiber is purchased from Taishan Glass Fiber Co., Ltd., with a model of T439; the polypropylene is purchased from Daqing Petrochemical Company of PetroChina, with a model of T30S; the polyimide is purchased from Mitsui Chemicals of Japan, with a model of PIPL6200; the maleic anhydride grafted polypropylene is purchased from Shanghai Rizhisheng New Technology Development Co., Ltd., with a model of CMG9801; the maleic anhydride grafted styrene butadiene styrene copolymer (SBS-g-MAH) is industrial grade and is purchased from Kraton Corporation of the United States; the nylon 6 resin is purchased from Xinhui Meida-DSM Nylon Chip Co., Ltd., with a brand of M25001; and other undisclosed raw materials and reagents are all commercially available.

[0034] The polypropylene composite materials in Examples 1-5 and Comparative Examples 1-4 were used as samples to conduct relevant performance tests, as follows: (1) Mechanical properties test: The impact strength test was carried out on an XCJD pendulum impact tester. The test standard was GB / T 1843-2008. Each sample was tested 3 times and the average value was taken. The tensile properties test was carried out on a WDW-1000G universal testing machine. The test standard was GB / T 1040.2-2022. Each sample was tested 3 times and the average value was taken. (2) Heat resistance test: The polypropylene composite material was made into a specimen with a size of 80 mm × 10 mm × 4 mm. The test standard was GB / T 1674.1-2004 and the load was 1.80 MPa. The above test results are shown in Table 1: Table 1

[0035] According to the test results in Table 1, it can be seen that the samples corresponding to Examples 1-5 of the present invention have excellent mechanical properties, excellent tensile properties and impact resistance, good toughness, and excellent heat resistance. In Comparative Example 1, the glass fiber was not modified, and the dispersibility and compatibility of the glass fiber deteriorated. In Comparative Example 2, the nano-calcium carbonate was not modified, and the dispersibility and compatibility of the nano-calcium carbonate deteriorated, and the comprehensive performance of the polypropylene composite material was reduced. In Comparative Example 3, the glass fiber and nano-calcium carbonate were directly added to the matrix, and the comprehensive performance of the obtained polypropylene composite material was greatly reduced. In Comparative Example 4, polyimide, nylon 6, and maleic anhydride grafted styrene butadiene styrene copolymer were not added, and the mechanical properties of the polypropylene composite material were reduced, and the heat resistance was less affected.

[0036] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a high-strength polypropylene composite material for a filter plate, characterized in that: The steps include: Step 1: Ultrasonically disperse nano calcium carbonate into deionized water, and after uniform dispersion, add L-lysine, heat, mix, and react. After the reaction is completed, filter, wash, and dry at 60° C. for 24 hours to obtain amino calcium carbonate; Step 2: Evenly mix the ethanol solution and γ-methacryloxypropyltrimethoxysilane, add glass fiber, stir, adjust the pH to 4.5, heat under reflux in a nitrogen atmosphere, react, and after the reaction is completed, filter, wash, and vacuum dry at 60° C. for 12 hours to obtain olefinic glass fiber; Step 3: Mix the olefinized glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, and acrylamide, add an initiator in a nitrogen atmosphere, heat and stir to react, wash after the reaction, and dry at 60° C. for 12 hours to obtain a modified glass fiber; Step 4: Evenly mix polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, amino calcium carbonate, modified glass fiber, antioxidant, and lubricant, perform melt blending, extrude, and cool to obtain a high-strength polypropylene composite material for filter plates.

2. The method for preparing a high-strength polypropylene composite material for a filter plate according to claim 1, characterized in that: In the step 1, the mass ratio of nano-calcium carbonate, deionized water and L-lysine is 100:1000-1500:8-15, the reaction temperature is 65-75° C., and the reaction time is 2-3 hours.

3. The method for preparing a high-strength polypropylene composite material for a filter plate according to claim 1, characterized in that: In the step 2, the mass ratio of the ethanol solution, γ-methacryloxypropyltrimethoxysilane and the glass fiber is 6800-7500:15-20:100, the reaction temperature is 95-105° C., and the reaction time is 4-6 hours.

4. The method for preparing a high-strength polypropylene composite material for a filter plate according to claim 1, characterized in that: In the step three, the mass ratio of olefinized glass fiber, anhydrous ethanol, acrylic acid, glycidyl methacrylate, acrylamide, and initiator is 100:3500-4500:25-35:8-15:6-10:2-5.

5. The method for preparing a high-strength polypropylene composite material for filter plates according to claim 1, characterized in that: The initiator in step 3 is benzoyl peroxide.

6. The method for preparing a high-strength polypropylene composite material for filter plates according to claim 1, characterized in that: The reaction temperature in step 3 is 75-85° C., and the reaction time is 2-4 hours.

7. The method for preparing a high-strength polypropylene composite material for a filter plate according to claim 1, characterized in that: In the step 4, the mass ratio of polypropylene, polyimide, maleic anhydride grafted polypropylene, nylon 6, maleic anhydride grafted styrene butadiene styrene copolymer, amino calcium carbonate, modified glass fiber, antioxidant, and lubricant is 100:12-18:2-5:1-2:3-5:3-7:6-10:0.2-0.5:0.1-0.

3.

8. The method for preparing a high-strength polypropylene composite material for filter plates according to claim 1, characterized in that: In step 4, the antioxidant includes one or more of antioxidant 168, antioxidant 1010, and antioxidant 1098, and the lubricant includes one or more of polypropylene wax, stearic acid acetamide, and polyethylene wax.

9. The method for preparing a high-strength polypropylene composite material for filter plates according to claim 1, characterized in that: In the step 4, the melt blending is carried out in a twin-screw extruder, the rotation speed of the twin-screw extruder is 140-150 rpm, and the twin-screw extruder is provided with five temperature zones according to the forward direction of the material, and the temperatures in the temperature zones are 135-150°C, 175-190°C, 205-215°C, 225-235°C, and 240-250°C, respectively.

10. A high-strength polypropylene composite material for filter plates prepared by the method for preparing a high-strength polypropylene composite material for filter plates according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-temperature-resistant and high-pressure-resistant filter plate of filter press and preparation method of filter plate

    CN108752738A

  • Filter press filter plate made of modified polypropylene composite material and continuous preparation method of filter press filter plate

    CN113637260A

  • Environment-friendly polypropylene material and preparation method thereof

    CN104650455A

  • Super-cold-resistant impact-resistant high-toughness PP-R pipe material and preparation method thereof

    CN104910521A

  • Resin composition, resin molded article, and method of preparing resin composition

    CN106554563A

Cited By

  • Modified high-strength polypropylene composite fiber and preparation method thereof

    CN119411240A

  • Calcium stearate emulsion as well as preparation method and application thereof

    CN120098328A

  • High-toughness anti-aging PP material and preparation method thereof

    CN121021982A

  • Mining light polymer conveyor scraper and preparation method thereof

    CN121317326A

  • Reinforced modified polypropylene cable conduit and preparation method thereof

    CN121554863A